Looking beyond the mountain: dispersal barriers in a changing world. Issue 5 (1st June 2016) - Caplat, Paul; Edelaar, Pim; Dudaniec, Rachael Y; Green, Andy J; Okamura, Beth; Cote, Julien; Ekroos, Johan; Jonsson, Per R; Löndahl, Jakob; Tesson, Sylvie VM; Petit, Eric J
Abstract : Dispersal barriers have demographic, evolutionary, and ecosystem‐wide consequences. With ongoing changes in the environment, some dispersal barriers will likely disappear while new ones will appear, and it is crucial to understand these dynamics to forecast species' distributions and adaptive potential. Here we review recent literature on the ecological and evolutionary aspects of dispersal to highlight key dynamics of dispersal barriers in the face of global change. After defining dispersal barriers, we explain that a better understanding of their dynamics requires identifying the barrier types that are most susceptible to change and predicting species' responses. This knowledge is a prerequisite for designing management strategies to increase or reduce connectivity, and maintain adaptive potential. Our intent is to motivate researchers to explicitly consider dispersal barriers in order to better forecast the dynamics of species and ecosystems subject to global change.